Further data on the establishment of Semielacher petiolatus ( Girault) (Hym. Eulophidae) in Sicily (Bollettino di zoologia agraria e bachicoltura, 2024)
From June to September 1999 samples of leaves infested by Citrus Leaf Miner(CLM) Phyllocnistis citrella Stainton were collected in citrus groves aroundPalermo, Agrigento, Trapani and Linosa Island in order to bred its Eulophid parasitoids.Asecodes delucchii (Boucek), A. erxias (Walker), Cirrospilus diallusWalker, C. pictus (Nees), C. vittatus Walker, Pnigalio agraules Walker and Semilacherpetiolatus (Girault) emerged. S. petiolatus has been found in ali the citrusgroves investigated, except the one located at Trapani territory. Furthermore itsrelative abundance was much higher than the ali other species together in the localitieswhere these latters emerged. During the investigations it was observed that4th CLM instar larvae may also be parasitized by S. petiolatus. These records onthis wasp look not only at its definitive establishment, but at its recovery also intothe biologica! niche previously occupied by severa! indigenous CLM' parasitoids.
Keywords: Phyllocnistis citrella; Semielacher petiolatus; controllo naturale